2022
DOI: 10.32615/ps.2022.002
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen rate and plant density interaction enhances grain yield by regulating the grain distribution of secondary branches on the panicle axis and photosynthesis in japonica rice

Abstract: Abbreviations: BFSB -filled grain number of secondary branches of the bottom panicle; BSB -grain number of secondary branches of the bottom panicle; Chl -chlorophyll; Ci -intercellular CO2 concentration; E -transpiration rate; F -filled grain rate; FGNSBfilled grain number of secondary branches; GNPB -grain number of primary branches; GNSB -grain number of secondary branches; GPP -grain number per panicle; gs -stomatal conductance; Ls -stomatal limitation value; MFSB -filled grain number of secondary branches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…In congruence with our results, the photosynthetic pigment contents were elevated ( Jinwen et al., 2009 ; Cisse et al., 2020 ; Hou et al., 2020 ) or showed an upward trend in indica hybrid rice ( Peng et al., 2021 ) and japonica rice ( Gong et al., 2022 ) with the increase in N application rates. Appropriate N application was shown to improve the enzyme and chlorophyll content of plant leaves, thereby improving the photosynthetic activities of the plant ( Giersch and Robinson, 1987 ; Nduwimana, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In congruence with our results, the photosynthetic pigment contents were elevated ( Jinwen et al., 2009 ; Cisse et al., 2020 ; Hou et al., 2020 ) or showed an upward trend in indica hybrid rice ( Peng et al., 2021 ) and japonica rice ( Gong et al., 2022 ) with the increase in N application rates. Appropriate N application was shown to improve the enzyme and chlorophyll content of plant leaves, thereby improving the photosynthetic activities of the plant ( Giersch and Robinson, 1987 ; Nduwimana, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Increased amounts of nitrate supply significantly enhanced Pn, g s , and E ( Mandal et al., 2022 ). As noted in this study, with the increase in N application level from 0 to 200 kg ha –1 , Pn, g s , and E were also increased gradually, while C i values were decreased ( Gong et al., 2022 ). Increased N application increased the Pn that noted a positive correlation with leaf N content ( Fallah, 2012 ; Rajesh et al., 2017 ; Bv et al., 2019 ; Zhang et al., 2020 ), increased the E ( Zhang et al., 2020 ), and increased the g s at the vegetative stage ( Roy Chowdhury et al., 2014 ).…”
Section: Discussionsupporting
confidence: 62%
“…Under the conditions of this experiment, the highest annual yield of double-season rice was found in the N2D3 plants ( Table 1 ). Many studies have shown that appropriate nitrogen fertilizer, appropriate density and a reasonable combination of the two can significantly increase the yield of rice [ 22 , 28 , 31 ]. Furthermore, the optimal amount of nitrogen fertilizer will vary according to the fertilizer tolerance of different rice varieties.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, if spikelets per panicle did not significantly increase under excessive use of nitrogen, the yield would be reduced due to poor grain filling [ 21 ]. A moderate reduction of nitrogen fertilization could prevent poor grain filling and reduce the number of panicles and spikelets, but dense planting would increase the number of panicles and spikelets [ 22 ]. Suitable nitrogen fertilizer could reverse damage caused by carbon-related metabolic enzymes and also regulate auxin and cytokinin, which contribute to grain filling, avoiding the damage of high-temperature grain filling and the consequences of poor grain filling caused by high nitrogen [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the increase in rice production in China will play an important role in its food industry. The amount of fertilizer and transplanting density are important factors that affect rice yield [2][3][4]. In China, hybrid rice cultivation generally adopts the planting mode of low density and a high fertilizer application rate to improve the rice yield [5].…”
Section: Introductionmentioning
confidence: 99%